2018
DOI: 10.1002/stem.2813
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Impairs Adipose Stromal Cell Vasculogenic Activity and Abrogates Potency to Ameliorate Ischemia

Abstract: Cigarette smoking (CS) adversely affects the physiologic function of endothelial progenitor, hematopoietic stem and progenitor cells. However, the effect of CS on the ability of adipose stem/stromal cells (ASC) to promote vasculogenesis and rescue perfusion in the context of ischemia is unknown. To evaluate this, ASC from nonsmokers (nCS-ASC) and smokers (CS-ASC), and their activity to promote perfusion in hindlimb ischemia models, as well as endothelial cell (EC) survival and vascular morphogenesis in vitro w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Nevertheless, there are still many hoops to jump ahead and a long way to get these therapies to move from clinical trials to FDA-approved treatments. One of the limitations for the usage of ASCs in regenerative medicine is the donor’s age, body mass index (BMI) and health conditions (underlying disease or comorbidities), which might result in reduced immunomodulatory abilities of main regulatory factors ( Strong et al, 2013 ; Barwinska et al, 2018 ). Thus, ASCs should be fully characterizing and thoroughly screened for in vitro aging and inflammatory markers that might affect their regenerative abilities and hinder their usage in clinical application.…”
Section: Future Applications For Ascsmentioning
confidence: 99%
“…Nevertheless, there are still many hoops to jump ahead and a long way to get these therapies to move from clinical trials to FDA-approved treatments. One of the limitations for the usage of ASCs in regenerative medicine is the donor’s age, body mass index (BMI) and health conditions (underlying disease or comorbidities), which might result in reduced immunomodulatory abilities of main regulatory factors ( Strong et al, 2013 ; Barwinska et al, 2018 ). Thus, ASCs should be fully characterizing and thoroughly screened for in vitro aging and inflammatory markers that might affect their regenerative abilities and hinder their usage in clinical application.…”
Section: Future Applications For Ascsmentioning
confidence: 99%
“…A study carried out by Barwinska et al (8) showed that ASCs isolated from smokers expressed lower anti-inflammatory and angiogenic factors but higher expression of the pro-inflammatory factor Activin A compared with ASCs obtained from nonsmokers. Thus the therapeutic potential, as well as the vasculogenic ability, of ASCs is compromised in smokers, as demonstrated both in vitro and in vivo models (8).…”
Section: Current Limitations In the Therapeutic Use Of Ascsmentioning
confidence: 99%
“…utilized a mouse HLI model to show that MSCs derived from smokers had significantly dampened angiogenesis, compared to nonsmokers [35]. In vitro experiments from the same study suggest a possible molecular mechanism involving activin A, whereby activin A diminishes secretion of hepatocyte growth factor and stromal derived factor-1 (Table 1).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%